Analysis of Perceived Benefit of Video on Demand Subscription - Rahmi; Amalia Nabila; Gusty Mutiara Medina (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
This study examines the perceived benefits of Video on Demand (VoD) services through two main dimensions: perceived usefulness and perceived enjoyment. A cross-sectional questionnaire survey design was adopted in this study. An online version of the survey was developed using Google Forms, and a survey link was generated. The 244 respondents of this study are those who are familiar with Video on Demand products. Analysis methods included validity and reliability testing using SPSS version 26, as well as calculating the weighted average and scale range to assess the effectiveness of perceived benefits. Results indicate that both dimensions, perceived usefulness and perceived enjoyment, fall into the "effective" category, with average scores of 4.14 and 3.98, respectively. The perceived usefulness dimension suggests that respondents find VoD valuable, especially due to the variety of available content, while the perceived enjoyment dimension shows that respondents find VoD reasonably enjoyable. This study provides insights for VoD industry players in Indonesia for developing marketing strategies, though it also acknowledges limitations such as the limited representativeness of the sample and the exclusion of external factors.